Numerical modelling of the interaction between flexible net panels and fluids using SPH method - Shi, Qian; Zhao, Depeng; Xue, Dawen; Zhang, Ning; Zhang, Lifeng; Pan, Yun (Frontiers in Marine Science, 2024)
A numerical approach based on Smoothed Particle Hydrodynamics(SPH) method is proposed to simulate the flow past flexible net panel. In this approach, the flexible net panels are modeled using a knot-spring model, in which, the nets are considered to be consist of physical net-knots structure with virtual elastic springs connecting them. The movement of the knots results in the deformation of the flexible nets. To validate this model, the obtained results are compared with existing experimental and simulation data. These comparisons demonstrate that the present model is suitable for simulating the flow past flexible net panels. The simulation can provide detailed velocity distribution of the flow and the deformation of the net panels. One advantage of the proposed approach over grid-based Eulerian methods is its ability to handle the challenges when the nets undergo large deformations or collide with other objects. The numerical approach shows promising potential for application in aquaculture facility engineering.